L’essai - Franck Renucci; David Galli (Communication)
In this work, the authors seek first to understand what a researcher experiences, before they tackle research writing per se. What makes this paper different is that it shows how researchers today are bereft of biological, psychological, and social guidance. Looking at people in this way leads the authors to think differently about research and its relationship to knowledge. The researcher’s body speaks and writes. The authors focus on trials and creative research where the researcher’s body, emotions, and feelings react to how they experience their relationship to others through temporalities, rhythms, and shifts